Effectiveness of Using Historical E-Maps to Improve Students' Skills in Identifying Continuity and Change - Mhd Asrian Syah; Ririn Darini; Arfaton; Nur Amelia Devi (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2026)
The ability to identify continuity and change is a fundamental dimension of historical thinking; however, history instruction in schools continues to emphasize factual knowledge, providing limited opportunities for students to develop this skill through interactive learning experiences. This study aimed to examine the effectiveness of Historical E-Map media in improving students’ skills in identifying continuity and change. A pretest–posttest control group experimental design was employed involving 50 twelfth-grade students at MAN 1 Kerinci selected through simple random sampling. Data were collected using a validated and reliable multiple-choice test and analyzed using an independent samples t-test and N-Gain analysis. The findings revealed a significant difference between the experimental and control groups (p = 0.001 < 0.05), indicating that the use of Historical E-Map had a positive effect on students’ historical thinking skills. The N-Gain score of 0.76 demonstrated a high level of improvement in students’ ability to identify continuity and change. These findings indicate that Historical E-Map is an effective instructional medium for fostering one of the core dimensions of historical thinking. The study recommends integrating Historical E-Map into history instruction to promote more interactive, inquiry-oriented, and spatially contextualized learning experiences.